Penerapan Sensor Infrared dalam Memberikan Instruksi Terhadap Gerbang Logika Pada Palang Pintu Otomatis - Lamsyah Abdil Hafiz (Jurnal Penelitian Rumpun Ilmu Teknik, 2022)
Changes in the pattern of human life today are mostly caused by the rapid development of technology which provides many forms of convenience in the use of devices or tools that are directly related to human life. We can prove this by increasing the number of new creativities emerging in the electrical world.